God, mind and authority in spinozian thought - Muhammet Mustafa Pepe; Uguz, Hülya Eski (Argumentos - Revista de Filosofia, 2023)
Religion has a relevant role in the framing of social life throughout human history. In all organized and non-organized societies, the influence of religion in the organization of the social life of the individual really great. In addition to the legal ties that bind people together in the society, religious ties are also important. In short, the statement “The history of humanity is shaped by the profound influence of religion” is a statement that should not be underestimated. This study is based on how Spinoza defines the concepts of God, mind and authority in his thought.